Satisfaction of the Patients and Attendances Getting Treatment from Upazila Health Complex of Patiya - Ghosh, Purnasree; Mahmud, Sayeed; Barua, Soumen; Chowdhury, Arna; Dutta, Shantanu; Urmi, Sharmin Sultana (IAHS Medical Journal, 2025)
Background: The best way to evaluate health care systems has been suggested to focus on patients' satisfaction with the medical care they receive. One effective method for creating more patient-centred approaches to healthcare delivery is to ask patients about their experiences with the quality of their primary care. The purpose of this study was to evaluate patients' satisfaction and its relation with some demographic factors of respondents in the Upazila Health Complex Patiya, Chattogram. Materials and methods: It was a descriptive type of cross-sectional study and data were collected from Patiya Upazila Health Complex, Chattogram from January 2024 to April 2024 by face-to-face interview. Results: In this sample of 250 participants, 139(55.6%) were patients and others were in attendances. Most of the participants were in the 30-49 years age group. 26(10.4%) participants were graduate and 33(13.2%) were illiterate. Maximum participants [105(42%)] were from the upper lower class. The majority of patients were satisfied with the facilities available as well as with the service of doctors (92%) and nurses (77.2%). 144 (57.6%) respondents were partly satisfied with the behaviour of MLSS/4th class office staff and 26 (10.4%) respondents were not at all satisfied. A significant association was found between educational qualification and the cleanliness of the hospital ( c2= 15.53, p 0.017). Conclusion: The provision of health care at this institution can be further enhanced by measuring the quality of care provided continuously and implementing tiny adjustments to enhance individual processes. IAHS Medical Journal Vol 7(2), December 2024; 64-68